Analisis Pengembangan Usaha Masyarakat Melalui Badan Usaha Milik Desa (BUMDES) (Studi Kasus Desa Tegal Gondo Kecamatan Purbolinggo Kabupaten Lampung Timur - Zeman, Muhammad Fadel; Lelawati, Nina (Jurnal Manajemen DIVERSIFIKASI, 2021)
Abstract The problem of equitable development lies in the village, making the village the spearhead of development in Indonesia. This has made the government continue to strive to encourage the village economy by distributing Village Funds and the Village-Owned Enterprise (BUMDes) development program. The success of Village-Owned Enterprises (BUMDes) is largely determined by the strategies adopted by the BUMDes managers or administrators. However, the current phenomenon is the fact that BUMDes has not optimally contributed to driving the village economy. The problem at BUMDes Tegal Gondo has not developed as planned. Several business units that are managed are underdeveloped and their responsibilities are unclear, and the impression is that BUMDes' financial management is not transparent. The purpose of this study was to analyze the financial and non-financial aspects of community business development through Village-Owned Enterprises, Village-Owned Enterprises, Tegal Gondo Village, Purbolinggo District, East Lampung Regency. The research design is quantitative and qualitative research. The method used in this research is explanatory survey method. The objects of this research are financial and non-financial aspects. This research activity was carried out at BUMDes, Tegal Gondo Village, Purbolinggo District, East Lampung Regency. The study population was the BUMDes management and the community of Tegal Gondo Village, Purbolinggo District, East Lampung Regency. Data collection techniques using interviews and documentation of BUMDes financial statements. The analytical tool used is to use financial and non-financial analysis. The results showed that from all aspects including market and marketing aspects, technical and technology aspects and management and human resources aspects, the results of the BUMDes Tegal Gondo business could be said to be feasible to be developed. The Pay Back Period value is below the predetermined time from the beginning, which is 2 years and 6 months. Net Present Value is positive. Net Benefit Cost Rate (Net BC) shows a value greater than one. Internal Rate Return shows a value greater than 9%. The Break Even Point has been exceeded with sales exceeding BEP of 5.92 tons per year, meaning that BUMDes in Tegal Gondo Village in general can still be developed. Keywords: Analysis of Community Business Development, BUMDes.